Differentiating and Managing Rare Thrombotic Microangiopathies During Pregnancy and Postpartum. Issue 1 (2nd January 2023) - Lim, Ming Y.; Abou-Ismail, Mouhamed Yazan; Branch, D. Ware
Abstract : Rare thrombotic microangiopathies can occur in pregnancy and require early diagnosis and prompt treatment to optimize maternal and fetal outcomes. Abstract : The most common thrombotic microangiopathy (TMA) of pregnancy is the well-recognized syndrome of preeclampsia with hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome. However, rare TMAs, including thrombotic thrombocytopenic purpura, complement-mediated hemolytic-uremic syndrome, and catastrophic antiphospholipid syndrome, may occur during pregnancy or postpartum and present with features similar to those of preeclampsia with severe features. Early recognition and treatment of these infrequently encountered conditions are key for avoiding serious maternal morbidities with long-term sequelae and possible maternal or fetal death. Differentiating between preeclampsia with severe features and these rare TMAs is diagnostically challenging as there is significant overlap in their clinical and laboratory presentation. Given the rarity of these TMAs, high-quality evidence-based recommendations on diagnosis and management during pregnancy are lacking. Using current objective information and recommendations from working groups, this report provides practical clinical approaches to diagnose and manage these rare TMAs. This report also discusses how to manage individuals with a history of these rare TMAs who are planning to conceive. To optimize favorable outcomes, a multidisciplinary approach including obstetricians, maternal-fetal medicine specialists, hematologists, and nephrologists alongside close clinical and laboratory monitoring is vital.